The Use of Constructions in The Novel The Autumn of The Patriarch by Gabriel Garcia Marquez - Sri Haryanti; Purwo Haryono; Ana Setyandari; Sukasih Ratna Widayanti (Jurnal Penelitian Humaniora, 2021)
The present study deals with the features of long sentences in the novel The Autumn of the Patriarch by Gabriel Garcia Marquez. This study aimed to identify the features of long sentences found in the novel and to suggest ways to comprehend the long sentences. This study is beneficial for the development of English teaching, particularly the structure course. The data were in the form of phrases, clauses, and sentences used in the novel which were collected through observation method (metode simak). Descriptive qualitative method was employed for analysing the data. The results indicated that most of the sentences were compound complex. Each clause can be identified through its subject, predicate, object, and adverb or complement. Each subordinate clause could be un-derstood by identifying the word(s) modified and introductory word used. By identifying the main clause, sub-ordinate clause, parts of a main clause, subordinate clause, and kinds of phrases, the reader can under-stand the long sentences. In addition, most of the main clauses were pre-ceded by adverbials.